MG/SI RATIOS OF AQUEOUS FLUIDS COEXISTING WITH FORSTERITE AND ENSTATITE BASED ON THE PHASE RELATIONS IN THE MG2SIO4-SIO 2-H2O SYSTEM - Kawamoto T.; Nishimura K.; Matsukage K.N.; Mibe K.; Isshiki M.; Ishimatsu N.; Ono S. (My University, 2004)
Direct observation of aqueous fluids coexisting with MgSiO3 (enstatite) and/or Mg2SiO4 (forsterite) was performed at 0.5–5.8 GPa and 800–1000 °C with an externally heated diamond-anvil cell and synchrotron X-rays. At 1000 °C in the MgSiO3 –H2O system, forsterite crystallizes below 3 GPa but not above that pressure. At 1000 °C in the Mg2SiO4 –H2O system, forsterite congruently dissolves into the aqueous fluids up to 5 GPa. These observations suggest that the aqueous fluids coexisting with enstatite and forsterite have Mg/Si < 1 below 3 GPa and 1 < Mg/Si < 2 above that pressure. Comparison with the previous studies reporting Mg/Si ratios of the aqueous fluid coexisting with enstatite and forsterite indicates that the Mg/Si ratios change rapidly from SiO2-rich to MgO-rich at around 3 GPa and 1000 °C. This change can be related to possible structural changes of liquid water under these conditions. The aqueous fluids coexisting with enstatite and forsterite do have Mg/Si ratios similar to those found in the partial melts of H2O-saturated peridotite. Somewhere within the upper mantle, these two fluids unite to form a single regime and cannot be distinguished from each other.
Keywords: enstatite; forsterite